3D Computed Tomography (3D-CT) Study of the Mandibular Foramen in Iraqi Adults (Bangladesh Journal of Medical Science, 2020)
Purpose: One of the extremely important mandibular anatomical landmarks is the Mandibular Foramen (MF). Knowledge the preciseposition of MF is essentialforramus surgical operations, administration of mandibular local anesthesia, and implants placement. This research was carried out to examine the precise location of MF in addition toevaluate the differences of its position between the right and left sides of the mandible and between males and females.Materials and Methods: This is a retrospective study based on CT gathered from CT database presented at the Radiology Department, Hospital of Hilla. Subjects were Iraqi adults with no craniofacial abnormalities. A total of 60 head and neck scans were collected. CT images were of high resolution and reconstructed into 3D. Analyses were carried out by using MIMICs v7.0 (Materialised Corporation, Belgium), on each side of the mandible, seven landmarks were chosen to determine the distances from these landmarks to MF.Results: The descriptive statisticalanalysis containing means, standard deviations, minimum and maximum values for each variable were calculated for right and left mandible separately in addition to males and females.There were no differences noticed between the right and left measurements for both genders. Most males measurements tended to have larger measurements than females.Conclusion: the MF location was highly variable amongst the Iraqi subjects. In both sides of the mandible, the MF position was more or less symmetrical and its position also displayed evidence of sexual dimorphism.Bangladesh Journal of Medical Science Vol.19(2) 2020 p.310-314